Pengaruh Pelatihan Komunikasi Terapeutik Perawat Terhadap Tindakan Keperawatan Di Perusahaan Jawatan Rumah Sakit Dr. Wahidin Sudirohusodo Makassar - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Background: The result of preliminary survei on July 2002 in Dr. Wahidin Sudirohusodo hospital of Makassar, found that therapeutic communication by nurses not yet optimal in nursing care practice. Rampiselal found similar problem in Dr. Sardjito Hospital Yogyakarta, which stated that there was a lack of response of the health care provider when patients and their families complained about their medication and nursing care. The aim of this research was to find out the influence of training with module, role-play with media CD toward the improvement of nurse's ability in having communication therapeutic in nursing implementation of activity. Methods: This research used a quasi experimental with nonequivalent control group design with pre-test and post-test. The subject of this research were 32 nurse that divided into 16 nurse who were given training with module method